BRAF mutations in non-small cell lung cancer: has finally Janus opened the door?. (May 2016) - Caparica, Rafael; de Castro, Gilberto; Gil-Bazo, Ignacio; Caglevic, Christian; Calogero, Raffaele; Giallombardo, Marco; Santos, Edgardo S.; Raez, Luis E.; Rolfo, Christian
Highlights: Clinical trials evaluating B-Raf inhibitors in BRAF+ NSCLC patients are described. Among BRAF inhibitors, new drugs in clinical development are shown. Overcoming resistance to BRAF inhibitors and immunotherapy, are also discussed. Abstract: B-Raf mutations occur in about 1–2% of non-small cell lung cancers (NSCLC). These mutations generate a permanent activation of the mitogen activated protein kinase (MAPK) pathway, which promotes tumor growth and proliferation. In the present review, we discuss B-Raf mutation epidemiology, diagnostic methods to detect B-Raf mutations, the role of B-Raf as a driver mutation and a potential therapeutic target in NSCLC. The results of clinical trials involving B-Raf or MAPK pathway inhibitors for the treatment of NSCLC are also discussed. Clinical trials evaluating B-Raf inhibitors in BRAF mutated NSCLC patients have shown promising results, and larger prospective studies are warranted to validate these findings. Enrollment of these patients in clinical trials is an interesting strategy to offer a potentially more effective and less toxic targeted therapy.